﻿A new Bolitoglossa (Amphibia, Caudata, Plethodontidae) from the Cordillera Oriental of Colombia - Yeny Rocio López-Perilla; Juan David Fernández-Roldán; Fabio Leonardo Meza-Joya; Guido Fabian Medina-Rangel (ZooKeys, 2023)
A new salamander species of the genus Bolitoglossa is here described from the cloud forests of the western slopes of the Cordillera Oriental of Colombia, in the Cundinamarca department. The most salient characters of this new species are its numerous maxillary and vomerine teeth, its moderate webbing on hands and feet, its short and robust tail, and its chromatic variation. Based on molecular analyses this new species is assigned to the adspersa species group and its status established as the sister species of B. adspersa, with which it was previously confused. Lastly, the distribution, natural history, and conservation status of the new species are discussed.